Origem e idades químicas U-Th-Pb dos distritos pegmatíticos de Itambé (BA) e Santa Maria de Itabira (MG) revelados pela monazita - Rafael de Magalhães Gomes Ferreira (2017)
Monazite is a phosphate light rare earth element [(LREE)PO4] that occurs as an accessory mineral in a wide variety of rocks, including granite, pegmatite, felsic volcanic ash, felsic gneiss, pelitic schist, gneiss of medium to high metamorphic grade, low-grade metasedimentay rocks, and as a detrital mineral in clastic and metaclastic sediments and carbonatites. This mineral contains negligible amounts of common lead (Pb), keeping only radiogenic Pb from Th and U of monazite. Compositional variations involving monazite in a ternary system with end members cheralite [CaTh(PO4)2], huttonite [ThSiO4] and monazite [REE(PO4)] occur their solid solutions. Backscattered electrons images and chemical microanalysis by electron microprobe were obtained from eight monazite crystals belonging to pegmatites to city of Itambé state of Bahia (Bananeira, Coqueiro I, Coqueiro II, Cavada and Paraíso) and three belonging to pegmatites to district of Santa Maria de Itabira state of Minas Gerais which are situated in the Eastern Brazilian Pegmatitic Province (EBPP). The monazite samples are part of context of the extensional collapse of the Araçuaí Orogen (Cambro-Ordovician) are compositionally homogeneous, with no internal domains/zoning and their U, Th and Pb because they are post-collisional to the Brasilian event. The average U-Th-Pb chemical age found in the Itambé monazites was 502 Ma, while in Santa Maria de Itabira it was on average 474 Ma. These values are compatible with compilations made by other authors in both regions by both isotopic methods and electron microprobe. The difference of the ages between the two Pegmatite Districts is around 30 Ma, which can be attributed to the duration time of the extensional collapse of the Orogen. Through the treatment of the mineral chemistry data obtained in electron microprobe (EM), it is concluded that the host pegmatites are products of partial melting of a basement wall rock (biotite-hornblende gneiss) that apparently represents a considerable portion of the substrate of the Araçuaí Orogen. The main chemical signature of these monazites corresponds to the enrichment of Samarium (Sm). Due to the partition coefficient of Sm in the essential minerals of this biotite-hornblende gneiss, it is suggested that at the moment of the relaxation of the involved structures, the partial melting of this rock would have occurred under adiabatic decompression, with the enrichment of this element in acidic magma, from which the monazite crystallized. In addition, the environment rich in aqueous fluids, originated from the dehydration of biotite and hornblende and decompression free space, allowed the abundant growth of the minerals during the formation of pegmatitic rocks of granitic composition. In this way, the monazite, besides being a geochronometer, can also be used as a petrogenetic indicator.